2017
DOI: 10.1021/acs.biochem.7b00265
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Microprotein–Protein Interactions via APEX Tagging

Abstract: Microproteins are peptides and small proteins encoded by small open reading frames (smORFs). Newer technologies have led to the recent discovery of hundreds to thousands of new microproteins. The biological functions of a few microproteins have been elucidated, and these microproteins have fundamental roles in biology ranging from limb development to muscle function, highlighting the value of characterizing these molecules. The identification of microprotein–protein interactions (MPIs) has proven to be a succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 42 publications
0
61
1
Order By: Relevance
“…Of note, hundreds or thousands of these so-called microproteins have been overlooked by genome annotation efforts 47 . Microproteins can regulate fundamental biological processes 48 , but their size makes it difficult to identify interaction partners 47,49 or to target them in mutagenesis screens 47 . Microprotein sequences also tend to be less conserved than those of longer protein-coding genes 50 .…”
Section: Proteomehd Contains Difficult-to-characterise Proteinsmentioning
confidence: 99%
“…Of note, hundreds or thousands of these so-called microproteins have been overlooked by genome annotation efforts 47 . Microproteins can regulate fundamental biological processes 48 , but their size makes it difficult to identify interaction partners 47,49 or to target them in mutagenesis screens 47 . Microprotein sequences also tend to be less conserved than those of longer protein-coding genes 50 .…”
Section: Proteomehd Contains Difficult-to-characterise Proteinsmentioning
confidence: 99%
“…Biotinylated proteins can be purified using avidin/streptavidin beads and are subsequently identified by mass spectrometry. Figures adapted from Ueda et al (2015) and Chu et al (2017). (C) PROTACs can be used to induce ubiquitination of a protein of interest followed by proteasome-dependent degradation.…”
Section: Proximity-dependent Biotin Identification (Bioid)mentioning
confidence: 99%
“…Such a problem thus demands a better approach for identifying micropeptide associated proteins and protein complexes. Recently Chu and colleagues applied an in-situ proximity tagging method to elucidate microprotein-protein interactions (MPIs) for an uncharacterized microprotein called c11orf98 (Chu et al, 2017 ). This method relies on an engineered ascorbate peroxidase (APEX) (Rhee et al, 2013 ).…”
Section: Functional Proteomicsmentioning
confidence: 99%
“…Since the interactions take place in the context of a living cell, the enrichment of nonspecific interactors is reduced. By applying this approach, it was revealed that c11orf98 interacts with nucleolar proteins nucleoplasm and nucleolin (Chu et al, 2017 ), which suggests that the application of APEX tagging is useful to characterize uncharacterized micropeptides.…”
Section: Functional Proteomicsmentioning
confidence: 99%